Do forest decision-makers in Southeastern Norway adapt forest management to climate change? - Heltorp, Kaja Mathilde Aamodt; Kangas, Annika; Hoen, Hans Fredrik (Taylor & Francis, 2018)
To study whether, why, and how forestry decision-makers in Southeastern Norway adapt to climate change, we conducted a series of semi-structured interviews in focus groups consisting of nonindustrial private forest owners, forest managers, and forest advisors. Our results show that a majority of the participants believed in climate change as a phenomenon, and had experienced events or observed changes that they attributed to climate change. However, we found little evidence of concern regarding climate change impacts on forest ecosystems and forestry among the participants. Instead, the majority regarded climate change more as an opportunity for the Norwegian forest-based sector than a threat. A minority had implemented proactive practices motivated by climate change but in all but one case, the adjustments were adaptation of forest infrastructure. In general, the participants agreed that the uncertainty associated with the effects of climate change and the (economical) uncertainty associated with adaptation of forest ecosystems were too large to change forest management practices at present. However, many participants, in particular the managers, are already adapting in response to experienced problems, such as increased frequency and duration of periods with low carrying capacity of the ground implying reduced or no accessibility within and to stands.
Keywords: risk perception; adaptive management; climate change; risk; management; risk management; forest management; forestry